Dental trauma prevalence and disability types: A comparative study among children and adolescents in Dharwad, India - Prajna Pramod Nayak; Prasad V Kakarla; Preetha J Shetty; Manohar Y Bhat (Wolters Kluwer Medknow Publications, 2015)
Introduction: Dental trauma (DT) has become an important attribute of dental public health. However, in the disabled population, the risks and consequences of DT have been barely studied. Aim: The aim was to assess and compare the prevalence of DT among disabled children and adolescents studying in special needs schools in the twin cities of Hubli-Dharwad, India. Materials and Methods: About 714 children and adolescents who were classified as visual impairment, speech and hearing (SH) disability, physical disability, mentally subnormal and multiple disabilities (MD) and in the age group of 4-19 years, studying in 14 special needs schools of Hubli-Dharwad were included. DT was recorded based on Ellis and Davey's classification. Association between the trauma prevalence and disability types were analyzed using Chi-square test. Results: The prevalence of DT was found to be 28.6%. MD children sustained highest trauma (40.90%) and SH children experienced lowest trauma (18%). Statistically significant association was found between trauma prevalence and gender, geographic location, anterior teeth protrusion and lip coverage. Maxillary central incisors were most affected, and Ellis class 1 fracture was the most common type of traumatic injury. None of the children had undergone any treatment for DT. Conclusions: This should alert caregivers to carry out intense investigation of the events, and there is a need to take up preventive measures by dental professionals and public health authorities to reduce this type of morbidity.